Writing : - Boutin, Marie-Christine (Oxford Univ. Press, 1994)
The book aims to familiarize students with some of the different forms of written English, including messages, diaries, letters, postcards and notes. The units are arranged thematically, and focus on the conversations and vocabulary od each type of writing activities.